Hidroponik sebagai Solusi Ketahanan Pangan di Lahan Terbatas Pelatihan Budidaya Tanaman Hidroponik Menuju Kemandirian Pangan Keluarga di Desa Pejangki - Adelia Razis Putri; Ais Munawaroh; Bela Septia Puspita; Erlangga Rafaeldy; Fery Fahidza Hasbulah; Figo Alzikri; Maulana Diva K; Nurlaila Nuzila; Reva Noviantica; Suci Lestari; Muhammad Fendrik (Yayasan Daarul Huda Kruengmane, 2026)
Limited land access remains a common constraint for households in rural areas seeking to meet their daily vegetable needs, a condition also faced by residents of Pejangki Village, Batang Cenaku District, Indragiri Hulu Regency. Hydroponics offers a practical solution to this constraint, as it requires no soil, uses water efficiently, and can be applied on narrow home yards. This article discusses the implementation of a hydroponic cultivation training program, a community service (KKN) activity carried out by students of Universitas Riau in Pejangki Village in 2026 in collaboration with the non-governmental organization Widya Erti Indonesia. The program was designed as a hands-on workshop introducing the concept, benefits, and basic techniques of hydroponic farming from preparing planting media and seeding to assembling simple pipe installations and mixing nutrient solutions targeting members of the Pejangki Berseri Women Farmers Group (KWT) together with village officials, the village security officer (Babinsa), and community leaders. Data were collected through participatory observation, brief interviews, and documentation during the activity. The results indicate strong enthusiasm and active participation among attendees, particularly KWT members, and suggest that the training has the potential to support household food security, reduce daily food expenses, and open new economic opportunities through the sale of fresh, harvest-ready vegetables.